The International Responsibility of States: Basis for the Defense of Human Rights - Díaz Cáceda, Joel (2008)
This paper develops what is the role of the State's international responsibility as the foundation of the defense of Human Rights. Currently, the general principles of the international responsibility of States are established; however, the problem of the origin of the problem has not been studied in depth. In this sense, the author analyzes what constitutes the international wrongful act, because international responsibility is a consequence of this. It is necessary to emphasize that it is associated to the figure of State, mainly, because it is the most important subject of international law; however, this does not exclude those of more subjects. In addition, the elements of international responsibility are developed. First, the elements that constitute the international illegal act are analyzed; Secondly, the types of obligations are distinguished: i) according to their nature and ii) according to the essential nature of the obligation violated. On the other hand, the author establishes the causes according to which international responsibility can be exonerated. These are developed in the draft of the International Law Commission and are essentially six: Consent, legitimate defense, countermeasures, force majeure, external danger and state of necessity. It is established that these are causes of justification; however, they do not cancel the obligation. As a last point, it analyzes what should be the reparations for illicit acts of the States. In this sense, it is concluded that, although opinion is divided, international jurisprudence establishes that States have the obligation to repair the damage caused, both material and moral. The reparation modalities are developed, which are, mainly, three: i) restoration of the previous situation, ii) compensation for damages and iii) satisfaction.